RECONSTRUCTION OF ONLINE LEARNING (CHALLENGES AND REINFORCEMENT OF LEARNING EVALUATION) - Muhlis Fajar Wicaksana; Sri Marmoah; Farida Nurhasanah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2024)
The SPADA Learning Machine System (LMS) of Bantara Sukoharjo Univet is an effort to optimize the teaching system during the COVID-19 pandemic. The aim of this research is to identify barriers and provide projections for strengthening online teaching in universities during the pandemic. A qualitative-descriptive approach is used in this research. The research sample focused on the Teaching and Education Faculty (FKIP) of Bantara Sukoharjo University was taken using a purposive sampling technique. Data collection was carried out through observation, interviews, and questionnaires. The data was then analyzed using three stages: data reduction, presentation, and drawing conclusions. Data source triangulation was applied to validate the data. The results of this study reveal several challenges in online learning, including (1) lecturers' limitations in mastering the SPADA system; 2) a lack of lecturer creativity in using SPADA in teaching; 3) inadequate materials or modules for online teaching; and 4) inadequate assessment instruments in the online teaching evaluation system. In addition, the projected strengthening of online teaching includes 1) a peer mentoring tutorial system for lecturers; 2) online discussions regarding periodic online teaching systems; and 3) the availability of tutorial guides for novice lecturers to operate SPADA LMS. This research concludes that teacher training experiences challenges in implementing SPADA LMS. Alternative solutions to these challenges must be formulated to maximize the implementation of online learning at universities.